Substitute Teachers. The Best of ERIC on Educational Management, Number 79 - ERIC Clearinghouse on Educational Management, Eugene, OR.; ERIC Clearinghouse on Educational Management (Syracuse, NY : ERIC Clearinghouse on Information and Technology, 1985)
This annotated bibliography reviews 12 publications dealing with substitute teaching, including an article listing at least five ways principals can avoid problems with substitute teachers, a guidebook providing detailed advice for substitute teachers, an article suggesting community people with special knowledge be called in as an alternative to hiring a substitute, two articles on increasing the effectiveness of substitute teachers, and a description and analysis of a college sociology professor's experiences as a substitute teacher. Other articles give advice for devising strategies to make substitutes an effective part of the school's mission; report the results of a comprehensive survey of substitute programs in 1,728 school districts; describe examples of innovative programs that have proved to be successful in improving the quality of substitute teaching; describe a Houston program for training effective substitutes; give advice to regular teachers, department chairpersons, and administrators on what exactly a substitute can or cannot do and on the cooperation necessary to integrate substitutes into the regular classroom without disruption; and offer a checklist to evaluate a substitute teacher program. (DCS)
Availability: Publication Sales, ERIC Clearinghouse on Educational Management, University of Oregon, Center for Advanced Technology in Education, 1787 Agate Street, Eugene, OR 97403 (single copies free).
Sponsoring Agency: National Inst. of Education (ED), Washington, DC.
Contract Number: 400-78-0007.
Educational level discussed: Elementary Secondary Education.
Administrators.
Practitioners.
Keywords: Cooperation; Educational Innovation; Educational Research; Elementary Secondary Education; Guides; Improvement Programs; Literature Reviews; Program Effectiveness; Program Evaluation; School Surveys; Substitute Teachers; Teacher Administrator Relationship; Teacher Effectiveness; ERIC Publications; Reference Materials, Bibliographies